Broad-based Participatory Inquiry into the Definition and Scope of Disaster - Fulya Ozturk Tasci; Ayse Oguz Unver (Seyit Ahmet Kıray, 2017)
Understanding what disaster means will not only raise our awareness but will also bring us closer to knowing how to protect ourselves in the face of their destructive effects. The aim of this study is to understand how the concept of disaster is perceived in different demographics/subgroups of the population and by defining the term, to determine its scope and contribute in the long term to the content and effectiveness of the disaster education in the school settings. The sample for the study, which was of survey design, comprised 1600 individuals. A "Disaster Definition and Scope Scale [DDSS]" developed by the researchers to inquire into the definition and scope of disasters was used as a data collection instrument. The Cronbach Alpha reliability coefficient for the internal consistency of the scale is .83. The frequency analysis method of statistical analysis was used to examine the participants' demographic features. The responses of the participants to the open-ended questions on the definition of disaster were examined under 4 main themes that categorized the responses as nature-based, people-based, belief-based and outcome-based.The third section made up of 25 items on the scope of the term disaster was analyzed using the one-way analysis of variance and the Scheffe's test was employed to ascertain the source of the significant differences between the groups in an inter-group post-hoc comparison. The conclusion of the study is that the concept of disaster is generally confused with natural phenomena in every aspects of the population and that the participants in the research were not even aware of the existence of institutions, associations and civil defense organizations that conduct disaster emergency operations. The media tools occupy an important place in providing the public with right disaster understanding.